Facile synthesis of para-[18F]fluorohippurate via iodonium ylide-mediated radiofluorination for PET renography. Issue 2 (15th January 2016) - Nkepang, Gregory N.; Hedrick, Andria F.; Awasthi, Vibhudutta; Gali, Hariprasad
Graphical abstract: Abstract: para -[ 18 F]fluorohippurate ([ 18 F]PFH) is a renal tubular agent suitable for conducting positron emission tomography (PET) renography. [ 18 F]PFH is currently synthesized by a four-step two-pot procedure utilizing a classical prosthetic group, N -succinimidyl-4-[ 18 F]fluorobenzoate, followed by glycine conjugation. Considering the short half-life of fluorine-18 (110 min), it is important to reduce the number of synthetic steps and overall production time for successful translation of any fluorine-18 radiopharmaceutical in to clinical practice. Here, we report a new two-step one-pot procedure using a novel spirocyclic iodonium ylide precursor for producing a dose of [ 18 F]PFH suitable for human use in 45 min including HPLC purification with an overall decay-corrected radiochemical yield of 46.4 ± 2.9% ( n  = 3) and radiochemical purity of >99%.